A metaficção historiográfica em Dias & dias, de Ana Miranda - Araujo, Cassiane Antoniolli de (2023)
This work aims to analyze the novel Dias e Dias, by Ana Miranda, with the main objective of identifying the characteristics of historiographic metafiction in the novel, focusing on the process of humanizing the poet Gonçalves Dias, the intertextuality, and the parody present in the work. Based on this, the analysis aims to understand how the reinterpretation of the past occurs, addressing not only the literary formation but also the historical formation of the country, through the historiographic metafiction proposed by Linda Hutcheon. When Ana Miranda incorporates the poetic work of Gonçalves Dias into the narrative, she contributes to the parody tradition and brings new contexts to his poetry. To support this study, it was necessary to discuss the boundaries between literature and history, as both are composed of discursive material. Also, the classic historical novel and the contemporary historical novel were discussed, highlighting some differences between these two genres. Moreover, the discussion about the characteristics of the metafiction and the historiographic metafiction is essential to identify such elements within the analyzed work. Finally, after the analysis of specific excerpts from the novel Dias e Dias, by Ana Miranda, it becomes evident that it is a contemporary historical novel that presents several elements of historiographic metafiction, such as parody, self-reflexivity, intertextuality, the presence of the historical past, and above all, the reconstruction of a certain event from another perspective - from the margin.